A laminated battery

CN122950641APending Publication Date: 2026-10-20ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510456347.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]本发明提供一种叠片电池,该叠片电池设置有表面层隔膜和中间层隔膜,将表面层隔膜用于单面正极,中间层隔膜用于双面正极,通过设置结构不同的表面层隔膜和中间层隔膜,解决因叠片电池不同区域的嵌锂速度不均衡而产生紫斑、析锂的问题

Benefits of technology

[0050]本发明提供的叠片电池在不同的位置区域设置了不同结构的隔膜,可以有效降低锂离子传输的阻力,提升锂离子传输性能,平衡叠片电池单面正极区域容易脱锂带来的嵌锂速度不均衡问题,不容易产生紫斑、析锂,从而提升叠片电池整体的倍率性能和循环性能;同时在电芯中电解液分布在表面更多,中间层隔膜位置更少,减少表面层隔膜的层数可以均衡表面与中间的电解液含量分布,从而进一步均衡电芯整体一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005355580830000171
    Figure BDA0005355580830000171
  • Figure BDA0005355580830000181
    Figure BDA0005355580830000181
  • Figure BDA0005355580830000201
    Figure BDA0005355580830000201
Patent Text Reader

Abstract

This invention provides a stacked battery, comprising a single-sided positive electrode, a surface layer separator, a negative electrode, N repeating layers, a surface layer separator, and a single-sided positive electrode stacked sequentially; wherein, each repeating layer comprises an intermediate layer separator, a double-sided positive electrode, an intermediate layer separator, and a negative electrode, where N≥1; the surface layer separator comprises a first base layer and a first polymer layer, the first polymer layer covering at least one side of the first base layer; the intermediate layer separator comprises a second base layer, a heat-resistant layer, and a second polymer layer, the heat-resistant layer covering at least one side of the second base layer; the second polymer layer is disposed as the outermost layer on at least one side of the intermediate layer separator. The stacked battery provided by this invention exhibits excellent cycle performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology and relates to a stacked battery. Background Technology

[0002] Lithium-ion batteries have advantages over other rechargeable batteries, such as high energy density, long cycle life, low self-discharge, and no memory effect. Therefore, they have been widely recognized and applied in the market since their introduction. As consumers use batteries more frequently, their requirements for battery charging and discharging speed and lifespan are also increasing.

[0003] Based on their internal structure and manufacturing process, lithium-ion batteries can be classified into cylindrical batteries and tandem batteries. Tandem batteries typically offer better energy density and generally have lower internal resistance, resulting in superior discharge performance and efficiency. However, the kinetics differ in different regions of tandem batteries, making them prone to purple spots and lithium plating issues. Summary of the Invention

[0004] This invention provides a stacked battery, which is provided with a surface layer separator and an intermediate layer separator. The surface layer separator is used for a single-sided positive electrode, and the intermediate layer separator is used for a double-sided positive electrode. By setting surface layer separators and intermediate layer separators with different structures, the problem of purple spots and lithium plating caused by uneven lithium intercalation rates in different regions of the stacked battery is solved.

[0005] In one aspect, the present invention provides a stacked battery, comprising a single-sided positive electrode, a surface layer separator, a negative electrode, N repeating layers, a surface layer separator, and a single-sided positive electrode stacked sequentially.

[0006] The repeating layer includes an intermediate layer membrane, a double-sided positive electrode, an intermediate layer membrane, and a negative electrode, where N≥1;

[0007] The surface layer membrane includes a first base layer and a first polymer layer, wherein the first polymer layer covers at least one side of the first base layer;

[0008] The intermediate layer membrane includes a second base layer, a heat-resistant layer, and a second polymer layer, wherein the heat-resistant layer covers at least one side of the second base layer; and the second polymer layer is disposed on the outermost layer of at least one side of the intermediate layer membrane.

[0009] In the stacked battery described above, the negative electrode includes a negative electrode current collector and a negative electrode coating covering at least one side of the negative electrode current collector;

[0010] The negative electrode coating has a recess on the side of its surface away from the negative electrode current collector.

[0011] In the stacked battery as described above, the projected area of ​​the recess on the negative electrode current collector is A1, the projected area of ​​the negative electrode coating on the negative electrode current collector is A2, and A1 / A2×100% is denoted as A; the porosity of the surface layer separator is P1; and the porosity of the intermediate layer separator is P2.

[0012] The stacked battery satisfies: 0.02≤A / (P1-P2)≤12.

[0013] The stacked battery described above satisfies at least one of the following conditions:

[0014] d) 0.6% ≤ A ≤ 60%;

[0015] e) 35% ≤ P1 ≤ 60%;

[0016] f) 30% ≤ P2 ≤ 50%.

[0017] As described above, in the stacked battery, the depth of the recess is H, the thickness of the second polymer layer is h, and the stacked battery satisfies 1.5≤H / h≤50.

[0018] For the stacked cells described above, 3μm≤H≤75μm and 0.5μm≤h≤8μm.

[0019] In the stacked battery described above, the surface layer separator satisfies at least one of the following conditions:

[0020] f) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the TD direction;

[0021] g) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the MD direction;

[0022] h) Tensile strength in the TD direction ≥ 50 MPa;

[0023] i) Tensile strength in the MD direction ≥ 50 MPa;

[0024] j) Puncture strength ≥ 150 kgf;

[0025] And / or, the intermediate layer membrane satisfies at least one of the following conditions:

[0026] f) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the TD direction;

[0027] g) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the MD direction;

[0028] h) Tensile strength in the TD direction ≥ 50 MPa;

[0029] i) Tensile strength in the MD direction ≥ 50 MPa;

[0030] j) Puncture intensity ≥ 150 kgf.

[0031] As described above, in the stacked battery, the first base layer comprises at least one of polyethylene, polypropylene, polyethylene and polypropylene composite material, polyamide, polyimide, and aramid.

[0032] And / or, the thickness of the first base layer is 3-12 μm;

[0033] And / or, the first polymer layer comprises a first polymer;

[0034] And / or, the thickness of the first polymer layer is 0.1-10 μm;

[0035] And / or, the areal density of the first polymer layer is 0.1 g / m³. 2 ~1g / m 2 ;

[0036] And / or, the second base layer comprises at least one of polyethylene, polypropylene, polyethylene and polypropylene composites, polyimide, and aramid;

[0037] And / or, the thickness of the second base layer is 3-12 μm;

[0038] And / or, the second polymer layer comprises a second polymer;

[0039] And / or, the areal density of the second polymer layer is 0.05 g / m³. 2 ~1g / m 2 .

[0040] In the stacked battery as described above, the heat-resistant layer comprises 80wt% to 99wt% inorganic particles and 1wt% to 20wt% binder;

[0041] The inorganic particles include at least one of alumina, magnesium oxide, boehmite, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide, aramid, and polyimide; the binder includes at least one of polyacrylate, polytetrafluoroethylene, polyvinylidene fluoride, hexafluoropropylene-vinylidene fluoride copolymer, polyimide, melamine salt, phosphate, pentaerythritol, triazine charring agent, polyacrylonitrile, and polymethyl methacrylate.

[0042] And / or, the thickness of the heat-resistant layer is 0.2-5 μm.

[0043] In the stacked battery described above, the first polymer includes at least one of polyethylene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile.

[0044] And / or, the number-average molecular weight of the first polymer is 100,000 to 800,000;

[0045] And / or, the first polymer is in particulate form, and the particle size Dv50 of the first polymer is 0.1 to 10 μm;

[0046] And / or, the second polymer includes at least one of polystyrene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile;

[0047] And / or, the number-average molecular weight of the second polymer is 100,000 to 500,000;

[0048] And / or, the second polymer is in particulate form, and the particle size Dv50 of the second polymer is 0.1 μm to 5 μm;

[0049] And / or, the softening point of the second polymer is 30°C to 80°C.

[0050] The stacked battery provided by this invention has separators with different structures in different locations, which can effectively reduce the resistance to lithium-ion transport, improve lithium-ion transport performance, balance the problem of uneven lithium insertion speed caused by easy lithium delithiation in the positive electrode area of ​​the single side of the stacked battery, and reduce the occurrence of purple spots and lithium plating, thereby improving the overall rate performance and cycle performance of the stacked battery. At the same time, the electrolyte is distributed more on the surface and less in the middle layer separator in the cell. Reducing the number of surface layer separators can balance the electrolyte content distribution on the surface and in the middle, thereby further balancing the overall consistency of the cell. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of a stacked battery according to a specific embodiment of the present invention;

[0052] Figure 2 This is a schematic diagram of the surface layer membrane in a specific embodiment of the present invention;

[0053] Figure 3 This is a schematic diagram of the surface layer membrane in another specific embodiment of the present invention;

[0054] Figure 4 This is a schematic diagram of the intermediate layer membrane in a specific embodiment of the present invention;

[0055] Figure 5This is a schematic diagram of the intermediate layer membrane in another specific embodiment of the present invention;

[0056] Figure 6 This is a schematic diagram of the intermediate layer membrane in another specific embodiment of the present invention;

[0057] Figure 7 This is a schematic diagram of the negative electrode in a specific embodiment of the present invention.

[0058] Explanation of reference numerals in the attached figures:

[0059] 1-Single-sided positive electrode; 2-Surface layer separator; 3-Negative electrode; 4-Intermediate layer separator; 5-Double-sided positive electrode; 6-Single-sided positive electrode; 7-Negative electrode; 8-Intermediate layer separator; 9-Surface layer separator; 21-First base layer; 22-First polymer layer; 31-Negative electrode current collector; 32-Negative electrode coating; 41-Second base layer; 42-Heat-resistant layer; 43-Second polymer layer; A-Recess. Detailed Implementation

[0060] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0061] Research has found that due to the structural design of stacked batteries, the single-sided positive electrode is prone to internal stress and curling because the positive electrode material is only coated on the current collector side. The curling direction is away from the stack core direction, which can easily cause the single-sided positive electrode to detach from the stack core, resulting in purple spots / lithium plating on the single-sided area, which in turn affects the cycle performance and safety performance of the battery.

[0062] Therefore, it is necessary to regulate the kinetics of different regions of the stacked battery to improve the problem of lithium plating in the single-sided positive electrode region, thereby improving the rate performance and cycle performance of the battery.

[0063] In one aspect, the present invention provides a stacked battery, comprising a single-sided positive electrode, a surface layer separator, a negative electrode, N repeating layers, a surface layer separator, and a single-sided positive electrode stacked sequentially.

[0064] The repeating layer includes an intermediate layer membrane, a double-sided positive electrode, an intermediate layer membrane, and a negative electrode, where N≥1;

[0065] The surface layer membrane includes a first base layer and a first polymer layer, wherein the first polymer layer covers at least one side of the first base layer;

[0066] The intermediate layer membrane includes a second base layer, a heat-resistant layer, and a second polymer layer, wherein the heat-resistant layer covers at least one side of the second base layer; and the second polymer layer is disposed on the outermost layer of at least one side of the intermediate layer membrane.

[0067] Specifically, the number of repeating layers N≥1, in one specific implementation, such as Figure 1 As shown, the number of repeating layers N=1, and the stacked battery includes a single-sided positive electrode 1, a surface layer separator 2, a negative electrode 3, an intermediate layer separator 4, a double-sided positive electrode 5, an intermediate layer separator 8, a negative electrode 7, a surface layer separator 9, and a single-sided positive electrode 6 stacked in sequence.

[0068] Among them, the single-sided positive electrode 1 and the single-sided positive electrode 6 mentioned above can be exactly the same, or they can differ in terms of thickness, composition ratio, etc.

[0069] In one specific embodiment, the single-sided positive electrode 1 and the single-sided positive electrode 6 are completely identical.

[0070] In addition, negative electrode 3 and negative electrode 7 can be exactly the same, or they can differ in thickness, composition ratio, etc.

[0071] In one specific embodiment, the negative electrode 3 and the negative electrode 7 are exactly the same.

[0072] In another specific embodiment, the number of repeating layers N=2, and the stacked battery includes a single-sided positive electrode, a surface layer separator, a negative electrode, an intermediate layer separator, a double-sided positive electrode, an intermediate layer separator, a negative electrode, an intermediate layer separator, a double-sided positive electrode, an intermediate layer separator, a negative electrode, a surface layer separator, and a single-sided positive electrode stacked in sequence.

[0073] In one specific embodiment, the positive electrode active material in the aforementioned single-sided positive electrode can be a type commonly used in the art, such as a positive electrode active material commonly used in lithium-ion batteries, for example, a composite oxide of lithium with at least one of cobalt, manganese, nickel, or combinations thereof. More specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based materials, etc. The positive electrode current collector material can be at least one of aluminum foil or nickel foil.

[0074] In one specific embodiment, the aforementioned single-sided positive electrode may further include a conductive agent and a binder. The conductive agent may be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder may be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.

[0075] like Figure 2 and Figure 3 As shown, the surface layer membrane 2 and / or the surface layer membrane 9 include a first base layer 21 and a first polymer layer 22, the first polymer layer 22 covering at least one side of the first base layer 21; as Figure 2 As shown, the first polymer layer 22 covers one side of the first base layer 21; as Figure 3 As shown, the first polymer layer 22 covers both sides of the first base layer 21.

[0076] like Figure 4 , Figure 5 , Figure 6 As shown, the intermediate layer membrane 4 and / or intermediate layer membrane 8 includes a second base layer 41, a heat-resistant layer 42, and a second polymer layer 43, with the heat-resistant layer 42 covering at least one side of the second base layer 41; the second polymer layer 43 is disposed on the outermost layer of at least one side of the intermediate layer membrane 4 and / or intermediate layer membrane 8.

[0077] The stacked battery provided by this invention exhibits excellent cycle performance and rate performance. This stacked battery comprises a surface layer separator and an intermediate layer separator. The surface layer separator is used on one side of the positive electrode, while the intermediate layer separator is used on both sides. By placing separators with different structures in different locations, the resistance to lithium-ion transport can be effectively reduced, improving lithium-ion transport performance. This balances the problem of uneven lithium insertion speed caused by the thicker aluminum foil in the stacked cells, which makes lithium delithiation more likely. It also reduces the likelihood of purple spots and lithium plating, thereby improving the overall rate performance and cycle performance of the stacked battery. Simultaneously, the electrolyte is distributed more on the surface of the cell, while the intermediate layer separator has fewer layers. Reducing the number of surface layer separators helps to balance the electrolyte content distribution on the surface and in the middle of the cell. By balancing the surface layer separator and the intermediate layer separator, the overall consistency of the cell is further balanced.

[0078] In one specific embodiment, the negative electrode includes a negative electrode current collector and a negative electrode coating covering at least one side of the negative electrode current collector;

[0079] The negative electrode coating has a recess on the side of its surface away from the negative electrode current collector.

[0080] like Figure 7 As shown, the recess A of the present invention is a cavity structure formed by the indentation of the surface of the negative electrode coating 32 away from the negative electrode current collector 31 towards the negative electrode current collector 31. Specifically, conventional methods in the art can be used to provide a cavity in the negative electrode coating. For example, mechanical wire bonding, laser wire bonding, electro- or thermal laser melting, radiation melting, chemical etching, friction wire bonding, and other processing methods can be used.

[0081] The number of recesses can be one or more. When there are multiple recesses, they are distributed along the length extension direction of the negative electrode, and any two recesses are independent of each other, without overlapping or covering each other, such as... Figure 7 As shown.

[0082] It should be noted that the present invention does not impose any special limitation on the three-dimensional shape of the recess A. When there are multiple recesses A, each recess A is set independently. For example, some recesses A have a triangular cross-sectional shape, and some recesses A have a rectangular cross-sectional shape.

[0083] By creating recesses on the surface, the lithium-ion transport channels can be increased, improving lithium-ion transport efficiency and thus enhancing the battery's rate performance and cycle performance.

[0084] The material of the negative electrode current collector layer can be at least one of copper foil, nickel foam, and copper foam.

[0085] It is understood that the negative electrode coating may include negative electrode active material, conductive agent, and binder. This invention does not limit the type of each component and can select materials commonly used in the field.

[0086] For example, the negative electrode active material can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), and tin-based negative electrode materials (mainly including tin and tin alloys). The conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0087] In one specific embodiment, the projected area of ​​the recess on the negative electrode current collector is A1, the projected area of ​​the negative electrode coating on the negative electrode current collector is A2, and A1 / A2×100% is denoted as A; the porosity of the surface layer membrane is P1; and the porosity of the intermediate layer membrane is P2.

[0088] The stacked battery satisfies: 0.02≤A / (P1-P2)≤12.

[0089] The projected area of ​​the concave portion on the negative electrode current collector refers to the area of ​​the overlapping part of the concave portion and the negative electrode current collector when the concave portion is projected orthogonally along the thickness direction of the negative electrode current collector; the projected area of ​​the negative electrode coating on the negative electrode current collector refers to the area of ​​the overlapping part of the negative electrode coating and the current collector when the negative electrode coating is projected orthogonally along the thickness direction of the negative electrode current collector.

[0090] On the one hand, a higher proportion of the negative electrode recess leads to a larger specific surface area of ​​the negative electrode. This increased surface area provides more active sites, which helps to improve the insertion and extraction rates of lithium ions, thereby improving the negative electrode kinetics. The higher the matching membrane porosity, the higher the kinetics and the less prone to lithium plating. Conversely, a lower proportion of the negative electrode recess leads to poorer negative electrode kinetics. A slightly lower matching porosity can reduce battery self-discharge and improve battery durability while meeting kinetic requirements. When this relationship is satisfied, the overall battery performance can be optimized, making it less prone to localized lithium plating and improving battery durability. When A / (P1-P2) is too large, the negative electrode recess area is too large, resulting in a loss of energy density and insufficient negative electrode active material, which weakens the ability to accept lithium ions extracted from the positive electrode, leading to lithium plating on the negative electrode surface or small differences in membrane porosity, resulting in localized lithium plating or large localized self-discharge. When A / (P1-P2) is too small, the negative electrode recess area is too small, resulting in insufficient negative electrode kinetics and easy lithium plating, or excessive porosity in the surface layer membrane, leading to large self-discharge in the corresponding area.

[0091] In one specific embodiment, the A1 / A2 test includes the following steps: the negative electrode sheet to be tested is sputter-coated with gold, and the surface of the negative electrode coating is observed using an electrolytic radiometric scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.). The total area of ​​the overlap between the negative electrode coating and the current collector in the field of view is recorded as the projected area A2, and the area of ​​the overlap between the concave part of the negative electrode coating and the negative electrode current collector is recorded as A1. The A1 / A2 area is calculated at 5 different locations, and the average value is taken to obtain A1 / A2.

[0092] In one specific embodiment, the test of P1 or P2 includes the following steps: placing different membrane samples to be tested into a mercury porosimeter, gradually increasing the mercury pressure, measuring the volume change of mercury, determining the pore volume distribution based on the mercury pressure and volume change curve, calculating the total volume of mercury pressed into the membrane, measuring the length, width, and height of the membrane sample to be tested using a micrometer, and calculating its total volume V. total V Hg and V total Substituting into the formula P=V Hg / V total The porosity is calculated by multiplying the result by 100%.

[0093] In one specific embodiment, the stacked battery satisfies at least one of the following conditions:

[0094] g) 0.6% ≤ A ≤ 60%;

[0095] h)35%≤P1≤60%;

[0096] i) 30% ≤ P2 ≤ 50%.

[0097] In one specific embodiment, the depth of the recess is H, the thickness of the second polymer layer is h, and the stacked battery satisfies 1.5≤H / h≤50.

[0098] The depth of the recess refers to the vertical distance between the highest and lowest points of the recess in the thickness direction of the negative electrode, while the thickness of the second polymer layer refers to the average thickness.

[0099] The present invention does not limit the testing method for the depth of the recess and the thickness of the second polymer layer; methods commonly used in the art can be selected for testing.

[0100] In one specific embodiment, the test of the recess depth includes the following steps: taking a negative electrode sample, cutting the cross-section of the negative electrode sample under freezing conditions (e.g., -80°C) using an ion beam polisher (e.g., Hitachi Arblade 5000); sputtering the negative electrode sample with gold, and then, referring to JY / T010-1996, using a scanning electron microscope (e.g., a Sigma 300 scanning electron microscope from ZEISS, Germany) to obtain a SEM image of the negative electrode cross-section (magnification can be 1000x to 30000x); taking the lowest point of the negative electrode recess image and the distance H1 perpendicular to the current collector from the farthest point of the negative electrode; continuously taking H2 and H3 at different recesses; and then the average value H of H1, H2, and H3 is the depth of the negative electrode recess.

[0101] The second polymer layer thickness test includes the following steps: a sample of a certain size (e.g., 15mm × 15mm) is cut from a selected area of ​​the intermediate layer separator. The separator sample is wrapped with copper foil and then cut under freezing conditions (e.g., -80℃) using an ion beam polisher (e.g., Hitachi Arblade 5000) to obtain the cross-section of the separator sample. The separator sample is then sputtered with gold, and then, referring to JY / T010-1996, a scanning electron microscope (e.g., Sigma300 scanning electron microscope from ZEISS, Germany) is used to scan and obtain the SEM image of the separator cross-section (magnification can be 1000x to 30000x). The farthest point and the closest point of the second polymer layer away from the second base layer are taken, and the distance h1 between the two points perpendicular to the substrate is measured. h2 and h3 are taken continuously in different recesses. The average value h of h1, h2 and h3 is the thickness of the second polymer layer.

[0102] When the relationship is satisfied, the recess increases the specific surface area of ​​the negative electrode. This increased surface area provides more active sites, which helps to improve the insertion and extraction rates of lithium ions, thereby improving lithium ion transport efficiency. At the same time, the interfacial adhesion between the separator and the electrode is excellent, the internal resistance of the battery is reduced, and the battery has high energy density and excellent rate and cycle performance. When H / h < 1.5, the recess depth is insufficient, the increase in active sites is limited, and the lithium ion transport efficiency cannot be improved well. Alternatively, if the thickness of the intermediate separator is too thick, the internal resistance of the battery increases, resulting in poor rate and cycle performance. When H / h > 50, the recess depth is too large, affecting the energy density of the battery. Alternatively, if the thickness of the intermediate separator is insufficient, it is easy to cause poor interfacial adhesion between the separator and the electrode, causing the interface to lose adhesion and deform during cycling, thus affecting the battery cycle performance.

[0103] Furthermore, in one specific embodiment, 3μm≤H≤75μm, 0.5μm≤h≤8μm.

[0104] When the recess depth and the thickness of the second polymer layer are within the above range, a better balance between rate performance and cycle performance can be achieved.

[0105] In one specific embodiment, the surface layer membrane satisfies at least one of the following conditions:

[0106] k) Bake at 130℃ for 1 hour, the thermal shrinkage rate in the TD direction is 1% to 50%;

[0107] l) Bake at 130℃ for 1 hour, the thermal shrinkage rate in the MD direction is 1% to 50%;

[0108] Tensile strength in the TD direction ≥ 50 MPa;

[0109] n) Tensile strength in the MD direction ≥ 50 MPa;

[0110] o) Puncture strength ≥ 150 kgf;

[0111] And / or, the intermediate layer membrane satisfies at least one of the following conditions:

[0112] k) Bake at 130℃ for 1 hour, the thermal shrinkage rate in the TD direction is 1% to 50%;

[0113] l) Bake at 130℃ for 1 hour, the thermal shrinkage rate in the MD direction is 1% to 50%;

[0114] Tensile strength in the TD direction ≥ 50 MPa;

[0115] n) Tensile strength in the MD direction ≥ 50 MPa;

[0116] o) Puncture strength ≥ 150 kgf.

[0117] In this invention, the TD direction refers to the transverse direction of the diaphragm, that is, the width direction of the diaphragm, while the MD direction refers to the longitudinal direction of the diaphragm, that is, the length direction of the diaphragm.

[0118] The thermal shrinkage rate, tensile strength and puncture strength of the intermediate layer diaphragm in the TD and MD directions can be determined using methods commonly used in the field.

[0119] For example, the thermal shrinkage rate of the surface layer membrane or the intermediate layer membrane can be measured by a method including the following process:

[0120] A sample of a certain size, usually rectangular or square, is cut from the diaphragm to be tested, ensuring that the edges of the sample are straight. The initial length of the sample in the TD direction is measured using calipers or a measuring microscope, and this length is recorded as L0. The sample is placed in a constant temperature oven and baked at 130°C for 1 hour. The sample is then removed from the 130°C oven and allowed to cool to room temperature. The length of the sample in the TD direction is measured again and recorded as L1. The thermal shrinkage rate in the TD direction is calculated as (L0-L1) / L0×100%. The thermal shrinkage rate test method in the MD direction is the same as that in the TD direction, except that L0 and L1 are replaced with the length values ​​in the MD direction.

[0121] For example, the tensile strength in the TD and MD directions of the surface layer membrane or the intermediate layer membrane can be tested with reference to the method in GB / T1040.3 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets".

[0122] For example, the puncture strength of the surface layer separator or the intermediate layer separator can be tested with reference to the method in GB / T36363-2018 "Polyolefin Separators for Lithium-ion Batteries".

[0123] When the parameters of the surface layer separator and the intermediate layer separator meet the above ranges in the TD and MD directions at 130°C, the intermediate layer separator ensures a certain level of stability and safety. Moderate thermal shrinkage can absorb some thermal stress during battery operation, preventing separator rupture or deformation, thereby improving battery safety and reliability. High tensile strength means the separator can withstand mechanical stress and deformation during battery assembly and operation, which helps prevent separator tearing or breakage, ensuring long battery life and stability. High puncture strength indicates the separator can resist puncture by external sharp objects, providing additional protection, especially when the battery is subjected to physical impact or compression.

[0124] In one specific embodiment, the first base layer includes at least one of polyethylene, polypropylene, polyethylene and polypropylene composites, polyamide, polyimide, and aramid. The first base layer of the above types can optimize the performance of the separator according to specific application requirements, including thermal stability, mechanical strength, chemical stability, and processability. The diverse material selection enables the separator to provide excellent performance and reliability in different battery applications.

[0125] In one specific embodiment, the thickness of the first base layer is 3-12 μm; more specifically, the thickness of the first base layer includes, but is not limited to, a range of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any two of these.

[0126] When the thickness of the first layer is within the above range, it can not only provide sufficient mechanical strength to effectively resist tearing and puncture and ensure the cycle performance of the battery, but also the thickness within the above range helps to reduce the impedance of ion transport, which helps to achieve faster charge and discharge speeds, thereby improving the ion conductivity and overall performance of the battery.

[0127] In one specific embodiment, the first polymer layer comprises a first polymer;

[0128] And / or, the thickness of the first polymer layer is 0.1-10 μm; more specifically, the thickness of the first polymer layer includes, but is not limited to, a range of 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any combination thereof.

[0129] When the thickness of the first polymer layer is within the above range, on the one hand, it can improve the interfacial compatibility and adhesion between the separator and the electrolyte, and enhance the cycle stability of the battery; on the other hand, it can minimize the obstruction to ion transport, improve the overall conductivity of the battery, and thus improve the rate performance and cycle performance of the battery.

[0130] In one specific embodiment, the areal density of the first polymer layer is 0.1 g / m³. 2 ~1g / m 2 Specifically, the areal density of the first polymer layer includes, but is not limited to, 0.1 g / m³. 2 0.2g / m 2 0.3g / m 2 0.4g / m 2 0.5g / m 2 0.6g / m 2 0.7g / m 2 0.8g / m 2 0.9g / m2 1.0g / m 2 .

[0131] When the areal density of the first polymer layer is within the above range, it helps to reduce the resistance to ion transport, improve the overall conductivity of the battery, and at the same time maintain the flexibility and adhesion of the separator, thereby improving the bonding performance of the material.

[0132] In one specific embodiment, the areal density testing method for the first polymer layer includes the following steps:

[0133] Cut a sample of the first polymer layer to a certain size, such as a 10cm × 10cm square, and denote the area as S = 100cm². 2 Weigh the first polymer layer sample using an electronic balance and record the data m. Calculate the areal density of the first polymer layer using the formula: areal density = m / S. Repeat this process three times and take the average value.

[0134] In one specific embodiment, the second base layer includes at least one of polyethylene, polypropylene, polyethylene and polypropylene composites, polyimide, and aramid; selecting one or more of these materials for the second base layer can optimize the performance of the diaphragm according to specific application requirements, including thermal stability, mechanical strength, chemical stability, and processability.

[0135] In one specific embodiment, the thickness of the second base layer is 3-12 μm; more specifically, the thickness of the second base layer includes, but is not limited to, a range of 3 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm or any two of these.

[0136] The second base layer within the aforementioned thickness range provides sufficient mechanical strength to resist tearing and puncture, while maintaining a certain degree of flexibility to facilitate battery assembly and handling. Moreover, the appropriate thickness helps to reduce the impedance of ion transport, thereby improving the ionic conductivity and overall performance of the battery.

[0137] In one specific embodiment, the second polymer layer comprises a second polymer; the areal density of the second polymer layer is 0.05 g / m³. 2 ~1g / m 2 Specifically, the areal density of the second polymer layer includes, but is not limited to, 0.05 g / m². 2 0.1g / m 2 0.2g / m 2 0.3g / m 2 0.4g / m 2 0.5g / m 2 0.6g / m 2 0.7g / m 2 0.8g / m 20.9g / m 2 1.0g / m 2 Or a range consisting of any two of them. Preferably, the areal density of the second polymer layer is 0.1 g / m³. 2 ~0.5g / m 2 .

[0138] The areal density of the second polymer layer is within the above range, which can provide sufficient adhesion to prevent the battery from softening and causing safety accidents. At the same time, it can ensure the transport of electrolyte, which is beneficial to the rate performance and cycle performance of lithium-ion batteries.

[0139] In one specific embodiment, the heat-resistant layer comprises 80wt% to 99wt% inorganic particles and 1wt% to 20wt% binder; exemplaryly, the inorganic particles include at least one of alumina, magnesium oxide, boehmite, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide, aramid, and polyimide; the binder includes at least one of polyacrylate, polytetrafluoroethylene, polyvinylidene fluoride, hexafluoropropylene-vinylidene fluoride copolymer, polyimide, melamine salt, phosphate, pentaerythritol, triazine charring agent, polyacrylonitrile, and polymethyl methacrylate; wherein, the above-mentioned inorganic particles help to improve the mechanical strength of the heat-resistant layer, enhance the tear resistance and puncture resistance of the diaphragm, and the above-mentioned binder can ensure the uniform distribution of particles, help to avoid local defects, and improve the overall performance of the diaphragm.

[0140] In one specific embodiment, the thickness of the heat-resistant layer is 0.2-5 μm.

[0141] In detail, the thickness of the heat-resistant layer includes, but is not limited to, a range of 0.2 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, or any combination thereof.

[0142] When the thickness of the heat-resistant layer is within the above range, it can better balance structural protection and ion conduction, ensuring good rate performance while guaranteeing battery cycle performance.

[0143] In one specific embodiment, the first polymer includes at least one of polyethylene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile; by selecting and combining these polymers, the first polymer layer can achieve a balance between chemical stability, thermal stability, mechanical properties, and electrical properties to meet the needs of different battery applications.

[0144] In one specific embodiment, the number-average molecular weight of the first polymer is 100,000 to 800,000; for example, the number-average molecular weight of the first polymer includes a range of 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000 or any two of these.

[0145] When the number-average molecular weight of the first polymer is within the above range, it means higher mechanical strength and toughness, which can enhance the durability and tear resistance of the separator, thereby improving the cycle performance of the battery.

[0146] And / or, the first polymer is in particulate form, and the particle size Dv50 of the first polymer is 0.1 to 10 μm; exemplaryly, the particle size Dv50 of the first polymer includes, but is not limited to, a range of 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any two of these.

[0147] When the particle size Dv50 of the first polymer is within the above range, the pore structure of the membrane can be optimized by adjusting the particle size, ensuring good ion conductivity and electrolyte permeability.

[0148] In one specific embodiment, the second polymer includes at least one of polystyrene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile.

[0149] In one specific embodiment, the number-average molecular weight of the second polymer is between 100,000 and 500,000; an appropriate molecular weight can ensure the electrical insulation properties of the polymer and prevent internal short circuits in the battery. Moreover, a number-average molecular weight in this range typically provides good mechanical strength and toughness, enhancing the tear and puncture resistance of the separator.

[0150] In one specific embodiment, the second polymer is in particulate form, and the particle size Dv50 of the second polymer is 0.1 μm to 5 μm. A suitable particle size range facilitates the uniform distribution of polymer particles on the substrate, forming a uniform coating. By adjusting the particle size, the pore structure of the membrane can be optimized, ensuring good ion conductivity and electrolyte permeability. By optimizing the particle size of the second polymer, the second polymer layer can play an important role in improving the mechanical properties, chemical stability, and electrical properties of the membrane.

[0151] In one specific embodiment, the softening point of the second polymer is 30°C to 80°C. More specifically, the softening point of the second polymer includes, but is not limited to, a range of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, or any combination thereof. Preferably, the softening point of the second polymer is 40°C to 70°C.

[0152] When the softening point of the second polymer is too low (e.g., below 30°C), the polymer will self-adhere and stick to the rollers during use, affecting the performance of the separator; when the softening point is too high (e.g., above 80°C), the polymer requires excessively high temperatures to achieve good adhesion, which will affect the solid electrolyte interface membrane and thus affect the performance of the lithium-ion battery.

[0153] In this invention, the Dv50 of the first polymer or the second polymer represents the particle size value corresponding to a cumulative amount of 50% (by volume) in the particle size cumulative distribution curve, which is generally obtained by testing with a laser diffraction particle size distribution instrument.

[0154] The stacked battery provided by the present invention will be described in detail below through specific embodiments.

[0155] Example 1

[0156] The fabrication process of the stacked battery provided in this embodiment includes the following steps:

[0157] 1. Preparation of the diaphragm:

[0158] 8 wt% of methacrylate polymer (the number average molecular weight of the methacrylate polymer is 100,000) and 92 wt% of auxiliary additives (composed of thickener sodium carboxymethyl cellulose, wetting agent dimethylsiloxane and binder methacrylic acid in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at a stirring speed of 1500 rpm for 60 min to obtain polymer slurry S1.

[0159] 8 wt% of vinylidene chloride polymer (with a number average molecular weight of 100,000) and 92 wt% of auxiliary additives (composed of sodium carboxymethyl cellulose thickener, dimethylsiloxane wetting agent, and methacrylic acid binder in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at 1500 rpm for 60 min to obtain polymer slurry S2.

[0160] Polymer S2 of 0.5 g / m² is coated on the first surface and the opposite second surface of a polyethylene substrate with a thickness of 7 μm and a porosity of 40%. After drying in an oven, a surface layer diaphragm comprising a first base layer and a first polymer layer is obtained. The diaphragm is baked at 130°C for 1 hour and has a thermal shrinkage rate of 1% in the TD direction and a tensile strength of 50 MPa. The thermal shrinkage rate in the MD direction is 1% and the tensile strength is 50 MPa. The puncture strength is 150 kgf.

[0161] A 1.5 μm thick alumina layer (composed of 95 wt% alumina, 4 wt% methacrylic acid, and 4 wt% sodium polymethyl cellulose) is coated on the first surface of a polyethylene substrate with a thickness of 3 μm and a porosity of 35%. Polymer S1 of 0.1 g / m² is coated on the second surface of the polyethylene substrate opposite to the first surface and on the surface of the alumina layer. After drying in an oven, an intermediate layer membrane comprising a second base layer, a heat-resistant layer, and a second polymer layer is obtained. After baking at 130°C for 1 hour, the membrane exhibits a 1% thermal shrinkage rate in the TD direction, a tensile strength of 50 MPa, a 1% thermal shrinkage rate in the MD direction, a tensile strength of 50 MPa, and a puncture strength of 150 kgf.

[0162] 2. Preparation of double-sided positive electrode: Lithium cobalt oxide, PVDF, and superconducting carbon black are placed in N-methylpyrrolidone at a mass ratio of 97:2:1 to prepare a positive electrode slurry. The positive electrode slurry is coated on both the front and back surfaces of the positive electrode current collector 2 (aluminum foil). After drying and rolling, a double-sided positive electrode is obtained.

[0163] 3. Preparation of a single-sided positive electrode:

[0164] Lithium cobalt oxide, PVDF, and superconducting carbon black were placed in N-methylpyrrolidone at a mass ratio of 97:2:1 to prepare a positive electrode slurry. The positive electrode slurry was then coated onto one surface of the positive electrode current collector 1 (aluminum foil). After drying and rolling, a single-sided positive electrode was obtained.

[0165] 4. Preparation of non-aqueous electrolyte: In an argon-filled glove box (moisture <10ppm, oxygen <1ppm), ethylene carbonate (EC), propylene carbonate (PC), and propyl propionate (PP) are mixed evenly in a mass ratio of 2:1.5:2. LiPF6 (14wt% based on the total mass of the non-aqueous electrolyte) and ethyl propionate (20wt% based on the total mass of the non-aqueous electrolyte) are slowly added to the mixed solution and stirred evenly to obtain the non-aqueous electrolyte.

[0166] 5. Preparation of the negative electrode: Graphite, styrene-diene rubber (SBR), sodium carboxymethyl cellulose, and conductive carbon black are mixed in a weight ratio of 94:3:2:1. The mixture is dispersed in water and then mixed using a double planetary mixer to obtain a negative electrode slurry. This slurry is coated onto a copper current collector, followed by drying, rolling, and laser wire bonding to obtain the negative electrode.

[0167] 6. Lithium-ion battery preparation: After stacking single-sided positive electrode, surface layer separator, negative electrode, intermediate layer separator, double-sided positive electrode, intermediate layer separator, negative electrode, surface layer separator, and single-sided positive electrode sheet in sequence, a bare cell is formed. Then, after processes such as encapsulation, cell baking, electrolyte injection, and hot pressing formation, the battery is obtained.

[0168] Example 2

[0169] The fabrication process of the stacked battery provided in this embodiment differs from that in Embodiment 1 only in that the fabrication of the separator includes:

[0170] 8 wt% of trifluorochloroethylene polymer (the number average molecular weight of the trifluorochloroethylene polymer is 800,000) and 92 wt% of auxiliary additives (composed of sodium carboxymethyl cellulose thickener, dimethylsiloxane wetting agent, and methacrylic acid binder in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at a stirring speed of 1500 rpm for 60 min to obtain polymer slurry S1.

[0171] 8 wt% of tetrachloroethylene polymer (with a number average molecular weight of 800,000) and 92 wt% of auxiliary additives (composed of sodium carboxymethyl cellulose thickener, dimethylsiloxane wetting agent, and methacrylic acid binder in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at 1500 rpm for 60 min to obtain polymer slurry S2.

[0172] A coating of 0.5 g / m² is applied to the first surface and the opposite second surface of a 12 μm thick polypropylene substrate with a porosity of 40%. 2 The polymer S2 is dried in an oven to obtain a surface layer membrane comprising a first base layer and a first polymer layer. After baking at 130°C for 1 hour, the membrane has a thermal shrinkage rate of 50% in the TD direction, a tensile strength of 70 MPa, a thermal shrinkage rate of 50% in the MD direction, a tensile strength of 70 MPa, and a puncture strength of 180 kgf.

[0173] A 5μm thick silica layer (composed of 80wt% silica, 4wt% polyimide, and 4wt% sodium polymethyl cellulose) is coated on the first surface of a 12μm thick polypropylene substrate with a porosity of 35%. 0.1g / m² of polymer S1 is coated on the second surface of the polyethylene substrate opposite the first surface and on the surface of the alumina layer. After drying in an oven, an intermediate layer membrane comprising a second base layer, a heat-resistant layer, and a second polymer layer is obtained. After baking at 130°C for 1 hour, the membrane exhibits a 50% thermal shrinkage rate in the TD direction, a tensile strength of 70MPa, a 50% thermal shrinkage rate in the MD direction, a tensile strength of 70MPa, and a puncture strength of 180kgf.

[0174] Example 3

[0175] The fabrication process of the stacked battery provided in this embodiment differs from that in Embodiment 1 only in that the fabrication of the separator includes:

[0176] 8 wt% of methacrylate polymer (the number average molecular weight of the methacrylate polymer is 500,000) and 92 wt% of auxiliary additives (composed of thickener sodium carboxymethyl cellulose, wetting agent dimethylsiloxane and binder methacrylic acid in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at a stirring speed of 1500 rpm for 60 min to obtain polymer slurry S1.

[0177] 8 wt% of vinylidene chloride polymer (with a number average molecular weight of 500,000) and 92 wt% of auxiliary additives (composed of sodium carboxymethyl cellulose thickener, dimethylsiloxane wetting agent, and methacrylic acid binder in a mass ratio of 2 wt%:1 wt%:5 wt%) were added to deionized water at a solid content of 10% and stirred at 1500 rpm for 60 min to obtain polymer slurry S2.

[0178] Polymer S2 of 0.5 g / m² is coated on the first surface and the opposite second surface of a polyethylene substrate with a thickness of 8 μm and a porosity of 40%. After drying in an oven, a surface layer membrane comprising a first base layer and a first polymer layer is obtained. The membrane is baked at 130°C for 1 hour and has a thermal shrinkage rate of 25% in the TD direction, a tensile strength of 100 MPa, a thermal shrinkage rate of 25% in the MD direction, a tensile strength of 100 MPa, and a puncture strength of 200 kgf.

[0179] A 3μm thick alumina layer (composed of 90wt% alumina, 4wt% polyvinylidene fluoride, and 4wt% sodium polymethyl cellulose) is coated on the first surface of a polyethylene substrate with a thickness of 8μm and a porosity of 35%. Polymer S1 of 0.1g / m² is coated on the second surface of the polyethylene substrate opposite to the first surface and on the surface of the alumina layer. After drying in an oven, an intermediate layer membrane comprising a second base layer, a heat-resistant layer, and a second polymer layer is obtained. After baking at 130°C for 1 hour, the membrane exhibits a 25% thermal shrinkage rate in the TD direction, a tensile strength of 100MPa, a 25% thermal shrinkage rate in the MD direction, a tensile strength of 100MPa, and a puncture strength of 200kgf.

[0180] Example 4-19

[0181] The preparation methods and raw materials of Examples 4-19 are basically the same as those of Example 3. Some examples have made certain adjustments in terms of raw materials and parameters, as detailed in Table 1.

[0182] Table 1

[0183]

[0184]

[0185] Comparative Example 1

[0186] The materials used in the stacked battery provided in this comparative example are basically the same as those in Example 1, except that the lithium-ion battery preparation process is different:

[0187] Lithium-ion battery manufacturing: A bare cell is formed by stacking a single-sided positive electrode, a surface layer separator, and a negative electrode in sequence. The battery is then produced through processes such as encapsulation, cell baking, electrolyte injection, and hot pressing.

[0188] Comparative Example 2

[0189] The materials used in the stacked battery provided in this comparative example are basically the same as those in Example 1, except that the lithium-ion battery preparation process is different:

[0190] Lithium-ion battery manufacturing: A bare cell is formed by stacking a single-sided positive electrode, intermediate layers of separator, and negative electrode sheet in sequence. The battery is then produced through processes such as encapsulation, cell baking, electrolyte injection, and hot pressing.

[0191] Comparative Example 3

[0192] The materials used in the stacked battery provided in this comparative example are basically the same as those in Example 1, except that the lithium-ion battery preparation process is different:

[0193] Lithium-ion battery manufacturing: A bare cell is formed by stacking a single-sided positive electrode, a surface layer separator, a negative electrode, a surface layer separator, a double-sided positive electrode, a surface layer separator, a negative electrode, a surface layer separator, and a single-sided positive electrode sheet in sequence. Then, the battery is obtained through processes such as packaging, cell baking, electrolyte injection, and hot pressing formation.

[0194] Test case

[0195] 1. Adhesion test between the intermediate layer diaphragm and the negative electrode:

[0196] After sorting the batteries obtained from the above embodiments and comparative examples, they were placed in an environment of (25±2)℃ and left to stand for 2-3 hours. The batteries were charged at a constant current of 0.7C with a cutoff current of 0.05C. When the battery terminal voltage reached the charging limit voltage, the charging was switched to constant voltage until the charging current was less than or equal to the cutoff current. The charging was then stopped and left to rest for 5 minutes. The fully charged batteries were then dissected. Using the national standard GB / T 2790-1995, the intermediate layer separator and the negative electrode sheet were cut into strips of 15mm×54.2mm. The adhesion between the intermediate layer separator and the negative electrode sheet was tested according to the 180° peel test standard. The test results are shown in Table 2.

[0197] 2. Loop testing

[0198] (1) 25℃ Cyclic Test

[0199] The initial voltage and initial thickness were tested sequentially using the batteries provided in all examples and comparative examples. The lithium-ion batteries were then placed at 25°C and charged at a constant current of 1C to the upper limit voltage (4.5V), followed by constant voltage charging at 4.5V to 0.05C, and allowed to rest for 5 minutes. Next, they were discharged at a constant current of 0.5C to 3V, and allowed to rest for 5 minutes; this constitutes one charge-discharge cycle. The capacity retention rate (%) of the lithium-ion battery after 1000T cycles was recorded. The final thickness was then tested, and the results are shown in Table 2.

[0200] (2) 20-week test of 5C / 6C direct charging

[0201] The lithium-ion battery was placed at 25℃±3℃ and charged at a constant current of 5C and 6C to the upper limit voltage (4.5V), then charged at a constant voltage of 4.5V to 0.05C and left to stand for 5 minutes. Next, it was discharged at a constant current of 0.5C to 3V, and the discharge capacity at this point was recorded as Q1. After standing for 5 minutes, this constituted one charge-discharge cycle. This charge / discharge cycle was repeated for 20 cycles. After 20 cycles, the battery was disassembled to check the lithium plating on the negative electrode corresponding to the positive electrode on one side. When the lithium plating area accounted for less than 3% of the total area of ​​the negative electrode, it indicated slight lithium plating; when the lithium plating area accounted for more than 10.5% of the total area of ​​the negative electrode, it indicated severe lithium plating; when the lithium plating area accounted for 3%-10% of the total area of ​​the negative electrode, it indicated lithium plating. The test results are shown in Table 2.

[0202] Table 2

[0203]

[0204] As shown in Table 2, compared with the comparative examples, the lithium plating of the stacked batteries provided in Examples 1-19 of the present invention is alleviated under the condition of 5C or 6C direct charging for 20T, the capacity retention rate (%) of 800T cycling at 25℃ is higher, and the thickness expansion rate (%) of 800T cycling at 25℃ is lower. This indicates that the technical solution provided by the present invention can significantly suppress lithium plating in the stacked batteries and improve the cycle performance and safety performance of the stacked batteries.

[0205] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A stacked battery, characterized in that, It includes a single-sided positive electrode, a surface layer separator, a negative electrode, N repeating layers, a surface layer separator, and a single-sided positive electrode arranged in sequence. The repeating layer includes an intermediate layer membrane, a double-sided positive electrode, an intermediate layer membrane, and a negative electrode, where N≥1; The surface layer membrane includes a first base layer and a first polymer layer, wherein the first polymer layer covers at least one side of the first base layer; The intermediate layer membrane includes a second base layer, a heat-resistant layer, and a second polymer layer, wherein the heat-resistant layer covers at least one side of the second base layer; and the second polymer layer is disposed on the outermost layer of at least one side of the intermediate layer membrane.

2. The stacked battery according to claim 1, characterized in that, The negative electrode includes a negative electrode current collector and a negative electrode coating covering at least one side of the negative electrode current collector; The negative electrode coating has a recess on the side of its surface away from the negative electrode current collector.

3. The stacked battery according to claim 2, characterized in that, The projected area of ​​the recess on the negative electrode current collector is A1, and the projected area of ​​the negative electrode coating on the negative electrode current collector is A2. A1 / A2×100% is denoted as A; the porosity of the surface layer membrane is P1; and the porosity of the intermediate layer membrane is P2. The stacked battery satisfies: 0.02≤A / (P1-P2)≤12.

4. The stacked battery according to claim 3, characterized in that, The stacked battery satisfies at least one of the following conditions: a) 0.6% ≤ A ≤ 60%; b) 35% ≤ P1 ≤ 60%; c) 30% ≤ P2 ≤ 50%.

5. The stacked battery according to claim 2, characterized in that, The depth of the recess is H, the thickness of the second polymer layer is h, and the stacked battery satisfies 1.5≤H / h≤50.

6. The stacked battery according to claim 5, characterized in that, 3μm≤H≤75μm, 0.5μm≤h≤8μm.

7. The stacked battery according to any one of claims 1-6, characterized in that, The surface layer membrane satisfies at least one of the following conditions: a) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the TD direction; b) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the MD direction; c) Tensile strength in the TD direction ≥ 50 MPa; d) Tensile strength in the MD direction ≥ 50 MPa; e) Puncture strength ≥ 150 kgf; And / or, the intermediate layer membrane satisfies at least one of the following conditions: a) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the TD direction; b) Bake at 130℃ for 1 hour, with a thermal shrinkage rate of 1% to 50% in the MD direction; c) Tensile strength in the TD direction ≥ 50 MPa; d) Tensile strength in the MD direction ≥ 50 MPa; e) Puncture strength ≥ 150 kgf.

8. The stacked battery according to any one of claims 1-6, characterized in that, The first base layer includes at least one of polyethylene, polypropylene, polyethylene and polypropylene composites, polyamide, polyimide, and aramid. And / or, the thickness of the first base layer is 3-12 μm; And / or, the first polymer layer comprises a first polymer; And / or, the thickness of the first polymer layer is 0.1-10 μm; And / or, the areal density of the first polymer layer is 0.1 g / m³. 2 ~1g / m 2 ; And / or, the second base layer comprises at least one of polyethylene, polypropylene, polyethylene and polypropylene composites, polyimide, and aramid; And / or, the thickness of the second base layer is 3-12 μm; And / or, the second polymer layer comprises a second polymer; And / or, the areal density of the second polymer layer is 0.05 g / m³. 2 ~1g / m 2 .

9. The stacked battery according to any one of claims 1-6, characterized in that, The heat-resistant layer comprises 80wt% to 99wt% inorganic particles and 1wt% to 20wt% binder; The inorganic particles include at least one of alumina, magnesium oxide, boehmite, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, nickel oxide, aramid, and polyimide; the binder includes at least one of polyacrylate, polytetrafluoroethylene, polyvinylidene fluoride, hexafluoropropylene-vinylidene fluoride copolymer, polyimide, melamine salt, phosphate, pentaerythritol, triazine charring agent, polyacrylonitrile, and polymethyl methacrylate. And / or, the thickness of the heat-resistant layer is 0.2-5 μm.

10. The stacked battery according to claim 8, characterized in that, The first polymer includes at least one of polyethylene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile; And / or, the number-average molecular weight of the first polymer is 100,000 to 800,000; And / or, the first polymer is in particulate form, and the particle size Dv50 of the first polymer is 0.1 to 10 μm; And / or, the second polymer includes at least one of polystyrene, polyvinyl chloride, perfluoropropylene, polychlorotrifluoroethylene, polytetrafluoroethylene, polyvinylidene chloride, polytetrachloroethylene, polyacrylate, polymethacrylic acid, polymethacrylate, and polyacrylonitrile; And / or, the number-average molecular weight of the second polymer is 100,000 to 500,000; And / or, the second polymer is in particulate form, and the particle size Dv50 of the second polymer is 0.1 μm to 5 μm; And / or, the softening point of the second polymer is 30°C to 80°C.